Ikiro-be alive : hedendaagse kunst uit Japan - 1980 tot heden. - Bremer, Jaap; Zijlmans, Kitty; van Straaten, Evert J. (Otterlo : Stichting Kröller-Müller Museum, 2001)
Akai, Fujio ; Hidaka, Rieko ; Kanemura, Osamu ; Kojima, Hisaya ; Kon, Yoshinori ; Koshimizu, Susumu ; Kuno, Toshihiro ; Lee, Ufan ; Miyajima, Tatsuo ; Mori, Mariko ; Ozawa Tsuyoshi ; Saitoh, Minako ; Shimabuku ; Suzuki, Takahiro ; Tabaimo ; Toya, Shigeo ; Tsuchiya, Kimio ; Wakabayashi, Isamu
kleine tekst per kunstenaar
Nederlands & Engels
Ikiro-be alive : hedendaagse kunst uit Japan - 1980 tot heden, Kröller-Müller Museum, Otterlo, 08.04 - 08.07.2001
boek
Keywords: Japan